TRANSAKSI ELEKTRONIK - Gunawan Widjaja; Hansel Kalama (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
Terms that are often found in society, such as e-commerce, e-business, and e-contract, essentially have differences from one another but are closely related. E-commerce is one way of running an e-business that is secured by an e-contract for the parties to one another. Meanwhile, e-business also has various models to run, each of which has a different way of doing it and different levels of preference from consumers. The issue of e-commerce has also become a concern for the international community with the demonstration of a general assembly resolution from the United Nations which regulates a little about e-commerce.